2017
DOI: 10.4103/0971-5851.203510
|View full text |Cite
|
Sign up to set email alerts
|

The role of chronic mucosal trauma in oral cancer: A review of literature

Abstract: Chronic mucosal trauma resulting from sharp teeth, dentures, faulty restoration, or implants has frequently been associated with the development of oral cancer. The definitive evidence for the same is lacking. We undertook a search using the terms – dental trauma, mucosal trauma, oral cancer, squamous cell carcinoma, risk factor, potentially malignant lesion, dental factor, mechanical irritation, dental irritation, and cancer in the following electronic databases: MEDLINE, PubMed, ScienceDirect, Cochrane Datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 41 publications
0
25
0
Order By: Relevance
“…The risk factors are well-known: smoking [ 3 ] and alcohol [ 4 ], which are considered modifiable major risk factors; others include the human papillomavirus (HPV) [ 5 , 6 ], poor oral hygiene [ 7 ], and chronic injuries of the mucosa [ 8 ]. Moreover, OSCC is easy detectable [ 9 ], thanks to the ease of inspection of the oral cavity and the frequent previous occurrence of oral potentially malignant disorders (OPMDs) including leukoplakia and erythroplakia, which are the most common ones [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors are well-known: smoking [ 3 ] and alcohol [ 4 ], which are considered modifiable major risk factors; others include the human papillomavirus (HPV) [ 5 , 6 ], poor oral hygiene [ 7 ], and chronic injuries of the mucosa [ 8 ]. Moreover, OSCC is easy detectable [ 9 ], thanks to the ease of inspection of the oral cavity and the frequent previous occurrence of oral potentially malignant disorders (OPMDs) including leukoplakia and erythroplakia, which are the most common ones [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many epidemiological studies have reported that chronic and heavy alcohol consumption, as well as poor oral hygiene, are strongly correlated with oral cancer 14 . However, in vitro studies have indicated that ethanol itself is not carcinogenic 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…In this study most patients were not associated with any dental factors. According to the study by (Chaturvedi et al, 2017) there is not enough available evidence which appears to be signi icant enough to support sharp teeth to be a risk factor in causing oral cancer. Many times, during the examination of oral cancer patients, we come across a sharp tooth at corresponding location on the alveolar arch.…”
Section: Resultsmentioning
confidence: 99%